2018
DOI: 10.1038/s41467-018-03347-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts induce antigen-specific deletion of CD8 + T Cells to protect tumour cells

Abstract: Tumours have developed strategies to interfere with most steps required for anti-tumour immune responses. Although many populations contribute to anti-tumour responses, tumour-infiltrating cytotoxic T cells dominate, hence, many suppressive strategies act to inhibit these. Tumour-associated T cells are frequently restricted to stromal zones rather than tumour islands, raising the possibility that the tumour microenvironment, where crosstalk between malignant and “normal” stromal cells exists, may be critical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
370
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(388 citation statements)
references
References 34 publications
15
370
3
Order By: Relevance
“…Cancer‐associated fibroblasts stimulate the growth and proliferation of tumour cells. Matthew et al found that CAFs activated an immune checkpoint to suppress the function of T cells, which was mediated by the engagement of PDL2 and FASL Therefore, CAFs contribute to the suppression of anti‐tumour T cell response by regulating immune cells, such as promoting antigen‐specific T cells death . Cancer‐associated fibroblasts can also promote the invasion and metastasis of tumour cells.…”
Section: Regulation Of Cancer‐associated Fibroblasts In Cancermentioning
confidence: 99%
“…Cancer‐associated fibroblasts stimulate the growth and proliferation of tumour cells. Matthew et al found that CAFs activated an immune checkpoint to suppress the function of T cells, which was mediated by the engagement of PDL2 and FASL Therefore, CAFs contribute to the suppression of anti‐tumour T cell response by regulating immune cells, such as promoting antigen‐specific T cells death . Cancer‐associated fibroblasts can also promote the invasion and metastasis of tumour cells.…”
Section: Regulation Of Cancer‐associated Fibroblasts In Cancermentioning
confidence: 99%
“…iSCs are known to interact directly with several subsets of haematopoietic immune cells in the intestine and may play a role in maintaining T cell tolerance at steady state . Furthermore, stromal cell signatures are known to correlate with poor therapeutic response in colorectal cancer, although it is not clear whether this results from stromal cell suppression of protective T cell responses, as seen in other tumour types …”
Section: Stromal Cells: Active Contributors To Immunity and Inflammationmentioning
confidence: 99%
“…In this review, I consider direct contacts of CAFs with cells of the immune system, which, in my opinion, are important for strengthening and guiding the action of paracrine factors. CAFs can establish direct contacts with immune cells and affect the efficiency of checkpoint immunotherapy by means of the expression of co‐inhibitory receptor ligands). By now, such a possibility was experimentally demonstrated for PD‐L1 and/or PD‐L2 expression (Figure A).…”
Section: From the Solid Base Of A Paradigm To A Flimsy But Falsifiablmentioning
confidence: 99%
“…However, most of these findings were made in in vitro experiments using isolated CAFs, and, therefore, require further studies to confirm the physiological significance of PD‐L1/L2 expression by CAFs for their immunosuppressive role in vivo . A recent paper, presents further evidence of the immuno‐inhibiting function of CAFs resulting from their direct interactions with immune cells. The authors show that CAFs can function as antigen presenting cells, able to absorb, process, and present on their surface tumor specific antigens complexed with MHC‐I proteins.…”
Section: From the Solid Base Of A Paradigm To A Flimsy But Falsifiablmentioning
confidence: 99%
See 1 more Smart Citation